Effect of Divalent Cations on the Interaction of Carboxylate Self-Assembled Monolayers - Rios-Carvajal, T (Langmuir : the ACS journal of surfaces and colloids, 2019)
Interactions between organic molecules in aqueous environments, whether in the fluid phase or adsorbed on solids, are often affected by the cations present in the solution. We investigated, at nanometer scale, how surface carboxylate interactions are influenced by dissolved divalent cations: Mg2+, Ca2+, Sr2+, and Ba2+. Self-assembled monolayer (SAM) surfaces with exposed terminations of alkyl, -CH3, carboxylate, -COO- , or dicarboxylate, -DiCOO-, were deposited on gold-coated tips and substrates. We used atomic force microscopy (AFM), in chemical force mapping (CFM) mode, to measure adhesion forces between various combinations of SAMs on the tip and substrate, in solutions of 0.5 M NaCl, that contained 0.012 M of one of the divalent cations. The type of cation, the number of carboxyl groups that interact, and their structure on the SAM influenced adhesion between the surfaces. The effect of the reference solution, which only contains Na+ cations, on adhesion force was mainly attributed to van der Waals and hydrophobic forces, explaining the lower force in systems that are more hydrophilic, i.e., -COO--COO-, and higher force for more hydrophobic systems. For charged surfaces, i.e., -COO- and -DiCOO-, in divalent cation solutions results were consistent with ion bridging. The inclusion of a hydrophobic surface, i.e., the -CH3-COO- or -CH3-DiCOO- system, decreased the possibility for strong cation bridging with the charged surface, resulting in lower adhesion. For systems including -COO-, the adhesion force series followed the inverse cation hydrated radius trend (Na+ ≈ Mg2+ < Sr2+ < Ca2+ < Ba2+) whereas -DiCOO- was responsible for lower adhesion force and modified trends, depending on the corresponding surface in the system. Differences in force magnitude between the monolayers were correlated with lower charge availability on the -DiCOO- surface as a result of fewer active sites, probably because of the tendency of exposed malonate surface groups to interact between them, as well as high rigidity, resulting from the molecule structure. The characteristic response of the -DiCOO- surface in solutions of Sr2+ and Ca2+ was correlated with possible malonate complexation modes. Comparison with previous studies suggested that the strong response of a -DiCOO- surface to Sr2+ resulted from bidentate chelation, whereas Ca2+ response was attributed to alpha-mode association to malonate